Experience reading. Book 2 - Liff, Suzanne; Stern, Joyce D (New York, NY : McGraw-Hill Higher Education, 2012)
Experience Reading engages students personally, actively, and critically through an integrated print and digital program designed to prepare them for college and lifelong reading
Includes bibliographical references and index
Keywords: College readers